2004
DOI: 10.1023/b:joor.0000018330.46029.05
|View full text |Cite
|
Sign up to set email alerts
|

Working Postures: A Literature Review

Abstract: Working postures are addressed in many papers in the ergonomics field but, surprisingly, scientific literature dealing with working posture itself is not common; knowledge has been elusive. This article reviews the working postures literature. Selected papers published in the English language before March 2003 including the phrase "working postures" in the title, abstract, or keywords were searched in the PubMed, Scirus, and Science Direct databases and reviewed. The literature provides evidence that working p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 55 publications
1
108
0
18
Order By: Relevance
“…The modified checkout workstation was equipped with a continuous conveyor belt in conjunction with a detection system as an alternative to allow checkout operators to handle products near their mid-line and minimize the need for trunk movements. It is known that movement range and working posture are relevant factors in occupational safety as they contribute to loading and injury risk 14,15,16 . Furthermore, these factors are of interest to professionals involved in minimizing/preventing risks of injury in occupational settings such as physical therapists, ergonomists and designers.…”
Section: Introductionmentioning
confidence: 99%
“…The modified checkout workstation was equipped with a continuous conveyor belt in conjunction with a detection system as an alternative to allow checkout operators to handle products near their mid-line and minimize the need for trunk movements. It is known that movement range and working posture are relevant factors in occupational safety as they contribute to loading and injury risk 14,15,16 . Furthermore, these factors are of interest to professionals involved in minimizing/preventing risks of injury in occupational settings such as physical therapists, ergonomists and designers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the advantages of sagittal posture measurements by inclinometer within the region of the lumbar spine [17,23]. Because the sonoSens Ò Monitor cannot assess sagittal trunk inclination independent of spine movements, it was necessary to integrate a sagittal inclinometer.…”
Section: Inclinometermentioning
confidence: 99%
“…The use of the same system in different workplaces, however, would enable the comparison of spine-related risk indicators [16]. Furthermore, to extend the knowledge about work-related spine loads as a predictor of low back pain, a valid and reliable measurement system is necessary to quantify data of trunk and spine postures and movements [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The main ergonomic risk factors for WRMSDs are: awkward posture, repetition, excessive physical load, forceful exertion, and duration of movement [8,9]. Moreover, arrangement of workstations, tasks and working methods, tools and anthropometric characteristics of workers have an influence on working postures [10]. The other problem is the adaptation of work stands to the elderly.…”
Section: Introductionmentioning
confidence: 99%